Optimal Modulation Algorithm for Hybrid Clamped Three-Level Inverter - Yi Liu; Guojun Tan; Xiaoqun He (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The principle of a three phase hybrid clamped three-level inverter was presented. Taking sixty-four switch states into consideration, the operational states of hybrid clamped three-level inverter and different current circuits in different switch states were detailed derived. Optimal modulation algorithm was proposed based on the neutral small vectors by different combination, which can realize the automatic balancing of the neutral-point voltage with few switching cycles and did not need to measure the voltage of the clamped capacitors. The proposed modulation algorithm was also capable of restraining the turn-off over-voltage of the power switching devices effectively. Simulation results were given to verify the feasibility and correctness. Experimental results obtained by DSP-based implementation of the controller on 1 MW prototype show good performance in terms of DC-bus voltages regulation (small neutral point potential function and low DC ripple coefficient) and good sinusoidal current.